Features of accounting of internal goodwill - Yasyshena, Valentyna; Pyliavets, Viktor (Herald of Economics, 2022)
Introduction. The inability to reliably determine the value of enterprises is due to the lack of methods of objective assessment of the intangible component of the enterprise, i.e. internal goodwill. Internal goodwill is one of the specific objects that is difficult to identify and evaluate, as well as to establish the reliability of the recognition of the economic benefits of its use. This exacerbates the relevance of current accounting of domestic goodwill in the enterprise.Purpose. Systematization and improvement of methodological approaches to accounting for internal goodwill, which should be taken into account to substantiate the scientific and applied principles in assessing the value of the company.Methods. The theoretical basis of the study is the scientific work of scientists on the study of goodwill, intellectual assets. The methodological basis of the study is general scientific methods (abstraction, comparison, generalization, grouping, systematization, analysis, synthesis) - to improve methodological approaches to accounting for internal goodwill. Schematic method is to summarize the intangible resources of the company and the relationship between them in accounting and disclosure of the impact of intangible and intellectual assets on the brand (brand) and value of the company. Abstract-logical method is to formulate research conclusions.Results. The necessity of separating the concepts of external and internal goodwill in the accounting is substantiated and their comparative analysis is carried out on the relevant grounds. The influence of intangible resources on the value of the enterprise in the system of financial and management accounting with the establishment of relationships between them is identified. The necessity of reflection of internal goodwill during all current activity of the company in the form of unaccounted intangible assets with assignment to the corresponding group of intellectual assets on analytical accounts in the system of financial and administrative accounting of the enterprise is substantiated. The necessity of keeping records of intellectual capital formed at the enterprise with the opening of relevant sub- accounts is substantiated. The method of accounting is revealed, which will allow to account for intellectual capital on external and internal goodwill in order to avoid underestimation of the real value of the enterprise and will not contradict the principles of full coverage and balance sheet.Discussion. At the regulatory level, it is necessary to develop methods for the recognition, evaluation, documentation, accounting and reflection in the financial statements of items included in the internal goodwill for their reflection in the financial accounting system.